The Effectiveness of the Student Teams Achievement Divisions (STAD) Cooperative Learning Model in Improving Students’ Arabic Writing Skills / Efektivitas Model Pembelajaran Kooperatif Student Teams Achievement Divisions (STAD) dalam Meningkatkan Keterampilan Menulis Bahasa Arab Siswa - Muhammad Fikri Aziz; R. Taufiqurrochman R. Taufiqurrochman; Nur Hasaniyah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study aimed to examine the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning model in improving students’ structured Arabic writing skills at Madrasah Aliyah Al-Khoiriyah Malang. This study employed a quantitative approach with a quasi-experimental, non-equivalent control group design. The participants consisted of 52 tenth-grade students divided into an experimental group (n = 27) and a control group (n = 25). The experimental group received instruction through the STAD model, whereas the control group received conventional instruction. Data were collected through pre-tests, post-tests, observation, and documentation. Students’ Arabic writing performance was assessed based on vocabulary selection, sentence construction, grammatical accuracy, spelling, organization, and neatness. The results showed that the mean score of the experimental group increased from 56.11 in the pre-test to 78.07 in the post-test, whereas the control group increased from 54.80 to 55.84. The mean N-Gain score was 0.51 for the experimental group, categorized as moderate, and 0.02 for the control group, categorized as low. The independent-samples test showed a statistically significant difference in post-test scores between the two groups (p < 0.001), while the Welch test also showed a significant difference in N-Gain scores (p < 0.001). These findings indicate that the STAD model produced significantly greater improvement in students structured Arabic writing performance than conventional instruction under the conditions of this quasi-experimental study. The findings suggest that STAD can support Arabic writing instruction through peer interaction, collaborative practice, individual accountability, and structured feedback.Penelitian ini bertujuan untuk menguji efektivitas model pembelajaran kooperatif Student Teams Achievement Divisions (STAD) dalam meningkatkan keterampilan menulis terstruktur bahasa Arab siswa di Madrasah Aliyah Al-Khoiriyah Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimental non-equivalent control group. Partisipan penelitian berjumlah 52 siswa kelas X yang terdiri atas kelompok eksperimen sebanyak 27 siswa dan kelompok kontrol sebanyak 25 siswa. Kelompok eksperimen memperoleh pembelajaran dengan model STAD, sedangkan kelompok kontrol memperoleh pembelajaran konvensional. Data dikumpulkan melalui pre-test, post-test, observasi, dan dokumentasi. Keterampilan menulis bahasa Arab dinilai berdasarkan pemilihan kosakata, konstruksi kalimat, ketepatan tata bahasa, ejaan, organisasi, dan kerapian. Hasil penelitian menunjukkan bahwa rata-rata skor kelompok eksperimen meningkat dari 56,11 pada pre-test menjadi 78,07 pada post-test, sedangkan kelompok kontrol meningkat dari 54,80 menjadi 55,84. Nilai rata-rata N-Gain kelompok eksperimen sebesar 0,51 dengan kategori sedang, sedangkan kelompok kontrol sebesar 0,02 dengan kategori rendah. Hasil uji beda menunjukkan adanya perbedaan yang signifikan secara statistik pada skor post-test antara kedua kelompok (p < 0,001). Uji Welch juga menunjukkan adanya perbedaan yang signifikan pada skor N-Gain (p < 0,001). Temuan ini menunjukkan bahwa model STAD menghasilkan peningkatan keterampilan menulis terstruktur bahasa Arab yang secara signifikan lebih besar dibandingkan pembelajaran konvensional dalam kondisi penelitian kuasi-eksperimental ini. Temuan tersebut menunjukkan bahwa STAD dapat mendukung pembelajaran menulis bahasa Arab melalui interaksi teman sebaya, latihan kolaboratif, tanggung jawab individual, dan umpan balik yang terstruktur.